Design and development of automation system for (clothes folding machine) / Bakr Saeed Riziq Daraghmeh - Bakr Saeed Riziq , Daraghmeh (2019)
Clothes folding machine is developed and designed to overcome the routine task of folding clothes, because of its highly requirement in our daily life use. The machine represented a fully automation system that combines the mechanical design with the electrical control design. the machine was developed to serve the normal people with a normal human intelligence so its design was completely representing the manual way of clothes folding, and specifically following the steps of folding the sleeves back ward then folding the lower shirt part and finally try to flip the shirt to its upper face on the way of delivering it to the operator. Shirts was taken as the first sample which the machine mechanisms designed to fold. Human intelligence was also required to overcome the obstacle of defining the clothes type and shape. So it was required by the operator to feed the clothes with a certain way, then allow the machine to fold it. Using the 3D simulation with the help of CAD engineering softwares (solidworks) boost the initial ideas to a desired point to go through the control part. PLC take a place to control the mechanisms with proper time folding and sequence. OMRON PLC CP1L model training kit hardware connected to the CX-Programmer software was the way of implementing the actual outputs for the machine parts movement before putting it in a prototype manner.